MOBSTER – VI. The crucial influence of rotation on the radio magnetospheres of hot stars. Issue 1 (27th April 2022) - Shultz, M E; Owocki, S P; ud-Doula, A; Biswas, A; Bohlender, D; Chandra, P; Das, B; David-Uraz, A; Khalack, V; Kochukhov, O; Landstreet, J D; Leto, P; et al.
ABSTRACT: Numerous magnetic hot stars exhibit gyrosynchrotron radio emission. The source electrons were previously thought to be accelerated to relativistic velocities in the current sheet formed in the middle magnetosphere by the wind opening magnetic field lines. However, a lack of dependence of radio luminosity on the wind power, and a strong dependence on rotation, has recently challenged this paradigm. We have collected all radio measurements of magnetic early-type stars available in the literature. When constraints on the magnetic field and/or the rotational period are not available, we have determined these using previously unpublished spectropolarimetric and photometric data. The result is the largest sample of magnetic stars with radio observations that has yet been analysed: 131 stars with rotational and magnetic constraints, of which 50 are radio-bright. We confirm an obvious dependence of gyrosynchrotron radiation on rotation, and furthermore find that accounting for rotation neatly separates stars with and without detected radio emission. There is a close correlation between H α emission strength and radio luminosity. These factors suggest that radio emission may be explained by the same mechanism responsible for H α emission from centrifugal magnetospheres, i.e. centrifugal breakout (CBO), however, while the H α-emitting magnetosphere probes the cool plasma before breakout, radio emission is a consequence of electrons accelerated in centrifugally driven magnetic reconnection.